The value of local climate and weather information: an economic valuation of the decentralised meteorological provision in Kenya. (7th February 2021) - Barrett, Sam; Ndegwa, William; Maggio, Giuseppe
ABSTRACT: The development of Sub-Saharan Africa will become increasingly constrained by the acute climate sensitivity of livelihood practices. Weather and climate services can improve climate risks to development by informing plans and decisions that ultimately reduce losses/maximize beneficial opportunities from climate variability and change. Yet, such services are typically highly aggregated, and notoriously difficult to communicate, especially to smallholder farmers and pastoralists where the need is greatest. Kenya Meteorological Department (KMD) are decentralizing service provision, and in so doing, offering disaggregated, contextualized, and more easily understandable localized weather and seasonal information products relative to national level equivalents. This article uses household productive income (2014–2015) across Kitui County to model the economic value of KMD's local seasonal forecast and advisory products. The findings suggest that, after controlling for alternative explanations, households receiving KMD's local advisories and seasonal forecasts have marginally higher income levels compared to the counterfactual of using national level equivalents. When marginal appreciations in productive income are compared to the costs of establishing and maintaining KMD's decentralized provision, the investment is economically viable and comparable with similar initiatives within and outside Kenya.